Magnetic transport properties of heavy fermionic EuNi2P2. (October 2019) - Wada, Hirofumi; Tanabe, Kosuke; Yamamoto, Ibuki; Mitsuda, Akihiro
Abstract: Electrical resistivity, magnetoresistance (MR) and Hall resistivity have been measured for Eu-based heavy fermion compound EuNi2 P2 (exact composition is Eu1.2 Ni2 P2.1 ). It is found that the 4 f electron contribution to the resistivity shows −log T above 200 K. The MR is positive at the lowest temperature and shows a negative minimum at around 60 K. The Hall resistivity shows a broad positive peak at around 120 K. These results are very similar to those of typical heavy fermions, CeCu6 and CeAl3 . We discuss the results in terms of the Kondo model for heavy fermions. Measurements under high pressures suggest that the scaling of the Hall effect is valid below 1.5 GPa in EuNi2 P2 . Highlights: The magnetic part of the electrical resistivity shows -log T dependence above 200 K. The magnetoresistance is positive at the lowest temperature and shows a negative minimum at around 60 K. The Hall resistivity is large and it shows a broad positive peak at around 120 K. The scaling of the Hall effect is valid below 1.5 GPa. We discussed the results of EuNi2P2 in terms of the Kondo model for heavy fermions.